Organic mass and protein extraction from secondary sewage sludge via multi-step physical alkali- and acid-based treatment - Skripsts, Eriks; Klaucans, Elvis; Mezule, Linda (Frontiers in Chemical Engineering, 2024)
The perception of sewage sludge has been shifting from waste to resource, leading to various technological proposals for its management and resource recovery. This study explores a two-step sewage sludge treatment using different pathways—physical-alkali followed by physical-acid, and physical-acid followed by physical-alkali hydrolysis—to understand the efficiency of organic matter (OM) and Kjeldahl nitrogen extraction, and protein solubilization. Hydrolysis of the sewage sludge was performed with 3 M H2SO4 and 2.8 M NaOH and combined with physical treatment—thermal, ultrasonication, microwave irradiation, and cavitation. The results showed that cavitation chemical hydrolysis in an alkaline environment (CCH-alkali) extracted the highest amount of OM—up to 79.0%. When further cavitation chemical hydrolysis in an acid environment (CCH alkali–acid) was performed, OM extraction reached 90.2%. Physical-alkali treatment showed better performance in resource recovery from secondary sludge (SS) in both treatment steps. The highest protein extraction rate of 23,046 mg/L in the supernatant was obtained using SS treatment with microwave chemical hydrolysis in an alkaline environment (MCH-alkali). Although physical-acid treatment resulted in reduced protein solubilization and OM extraction, it provides a higher protein hydrolysis rate. Organic nitrogen compounds were better extracted with thermal-alkali treatment, reaching 95.3% removal. The study showed that different physical treatment methods demonstrate selective resource recovery or extraction performance.